PARTICIPATORY LEADERSHIP AMONG SCOUT LEADERS WHO RECEIVED THE WOODEN BADGE IN IRAQ - Ghayth Dhamin Ramadan; Assist. Prof. Dr. Salem Khalaf Fahad; Assist. Prof. Dr. Buthaina Hussein Ali (American Journals, 2023)
The study aims to:Building a scale of participatory leadership among scout leaders who obtained the wooden badge in Iraq- Identifying the level of participatory leadership among the scout leaders who obtained the wooden badge in IraqIdentify the differences in participatory leadership among scout leaders according to years of service- Identifying the differences in participatory leadership among scout leaders according to academic qualification.Identify the differences in participatory leadership among scout leaders by genderThe researcher used the descriptive survey method due to its suitability to the nature of the researchThe research community included leaders who obtained the wooden badge in Iraq except for the Kurdistan Region of Iraq, as the total number of the research community reached (352) male and female leaders distributed over the Directorate of Sports and Scout Activity in all governorates of Iraq except for the governorates of the Kurdistan Region of Iraq.The sample was chosen by the intentional method and by the method of comprehensive enumeration from the leaders who obtained the wooden badge in Iraq, except for the Kurdistan Region of Iraq, whose number is (226) male and female leaders distributed among the education directorates in the governorates of Iraq, which represents (69%) of the total research community